Ages and sources of detrital zircons from the Early Mesozoic metasedimentary rocks of the Un’ya-Bom terrane of the Mongol-Okhotsk fold belt: results of U-Th-Pb and Lu-Hf isotope studies - V. A. Zaika; A. A. Sorokin (Геодинамика и тектонофизика, 2019)
The U-Pb and Lu-Hf isotope studies have been performed to investigate detrital zircons from metaterrigenous deposits (Nel, Kurnal and Amkan formations) of the Un’ya-Bom terrane of the eastern part of the Mongol-Okhotsk fold belt. The concordant ages of the youngest zircon in the metasiltstone of the studiedformations are as follows: 213±3.6 Ma –Nel, 194±4.4 Ma –Kurnal, and 202±2.5 Ma – Amkan. The new data suggest that a previouslyassumed(Middle Jurassic) age of the Amkan formation is uncertain. Most likely, the Kurnal and Amkan formations are of the same (Early Jurassic) age. In any case, a relationship between these formations needs to be clarified. In combination with the data from previous studies of the Tukuringra terrane, our study results show that the Early Mesozoic sedimentary rocks in the structure of the eastern part of the Mongol-Okhotsk fold belt are more abundant than it is currently assumed. Our study results suggest that during the accumulation of the Nel, Kurnal and Amkan formations, the materials were supplied from different provinces, especially from the Amur superterrane (i.e. from the south, in modern coordinates), as well as from the frame of the North Asian craton (i.e from the north, in modern coordinates), although the contribution of the craton source was insignificant.